Improving protection of victims' rights: access to lega aid - Redakcja (My University, 2014)
The book focuses on the access to justice of victims of crime, especially through the identification of common criteria for the legal aid to victims to be applied in harmonization of EU legislation, and namely with reference to the adoption of the DIRECTIVE 2012/29/EU OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL of 25 October 2012 establishing minimum standards on the rights, support and protection of victims of crime.
Keywords: DIRECTIVE 2012/29/EU OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL of 25 October 2012